2008
DOI: 10.1097/aco.0b013e32830a4bfd
|View full text |Cite
|
Sign up to set email alerts
|

Progress in pain assessment: the cognitively compromised patient

Abstract: Purpose of review-Pain assessment is essential for patient care in many settings, but it proves difficult when the patient is cognitively compromised or otherwise unable to produce a conventional pain report. This review describes progress in pain assessment technology that involves the coding of human facial expression.Recent findings-It is possible to quantify facial expression by coding patterns of facial muscle contraction and relaxation. These patterns are action units, and they can gauge the intensity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…All the participants in our sample had clear verbal communication problems and severe cognitive impairments. This is significant, as older populations with mild to moderate dementia do not express their pain (via facial expression) as strongly as do older adult populations with moderate to severe dementia [55–57]. Furthermore, our sample of participants was very inclined to present with pain behavior during transfers/mobilizations, as almost all of the recruited residents were receiving analgesics prior to the beginning of the study.…”
Section: Discussionmentioning
confidence: 97%
“…All the participants in our sample had clear verbal communication problems and severe cognitive impairments. This is significant, as older populations with mild to moderate dementia do not express their pain (via facial expression) as strongly as do older adult populations with moderate to severe dementia [55–57]. Furthermore, our sample of participants was very inclined to present with pain behavior during transfers/mobilizations, as almost all of the recruited residents were receiving analgesics prior to the beginning of the study.…”
Section: Discussionmentioning
confidence: 97%
“…48 In the last 35 years, more than 35 pain assessment instruments for older persons with dementia have been developed, tested, and reviewed in the literature. 19,20,[48][49][50][51][53][54][55] Most of these instruments are based on the idea that the patients' acute or chronic pain experience is communicated by changes in facial expression, vocalization, and body movements. 22 It has also been suggested that one of the primary functions of pain behaviour is to elicit the aid of others.…”
Section: Dementiamentioning
confidence: 99%
“…Research is ongoing to refine relevant indicators and establish tools to measure pain in nonverbal older adults. Frequency of behavior presentation and key behaviors, such as facial grimacing or expression, are beginning to emerge as important factors to detect and judge severity of pain in those with dementia [56–58].…”
Section: Introductionmentioning
confidence: 99%